2012
DOI: 10.1016/j.ijgo.2012.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic changes in the placentas of HIV‐positive women and their association with degree of immune suppression

Abstract: Both macroscopic and microscopic differences relating to the degree of immune suppression were identified, which seemingly contradicts previous reports. Larger studies are warranted to define the function of antiretroviral therapy and VUE in the mechanism of mother-to-fetus transmission of HIV. Furthermore, the potential role of VUE in the pathophysiology of the compromised immune response observed among HIV-exposed but uninfected infants should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…However, results were not correlated with CD4 count . A Cape Town hospital‐based study including stillbirths found an increased prevalence of the lesion in women with low CD4 counts but preceded the more effective PMTCT strategies in place during our study. Baurakiades et al ., commenting on the increased numbers of CD8+ T cells observed in the placenta of HIV‐infected women, postulated the presence of an HIV‐specific villitis, distinct from VUE .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, results were not correlated with CD4 count . A Cape Town hospital‐based study including stillbirths found an increased prevalence of the lesion in women with low CD4 counts but preceded the more effective PMTCT strategies in place during our study. Baurakiades et al ., commenting on the increased numbers of CD8+ T cells observed in the placenta of HIV‐infected women, postulated the presence of an HIV‐specific villitis, distinct from VUE .…”
Section: Discussionmentioning
confidence: 57%
“…We present, to our knowledge, the largest analysis of placentas from a well‐matched group of HIV‐infected and HIV‐negative women experiencing uncomplicated vaginal deliveries at term in a resource‐limited setting . This limits much of the confounding owing to gestational age and obstetric complications seen in hospital‐based populations in other studies , allowing us to generalise to similar healthy populations. Moreover, HIV‐infected and HIV‐negative women were from the same communities and similar in their socio‐economic, behavioural and cultural characteristics, thus further limiting unmeasured confounders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Prenatal exposures to infections, including HIV, may alter fetal and postnatal growth, 2 through decreases in placental size or morphologic changes 3,4 or mitochondrial abnormalities. 5 Little is known about antenatal ARV exposure and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal HIV may restrict placental size (7, 8) and cause morphologic changes,(8, 9) leading to deficient nutrient transfer and aberrant fetal metabolism. Metabolic complications from these changes may include compromised intrauterine and postnatal growth from placental insufficiency, poor bone health from decreased vitamin D and calcium transfer, as well as mitochondrial toxicities attributed to ARV exposure.…”
mentioning
confidence: 99%